The costs of working in Ireland - Niamh Crilly; Anne Pentecost; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2012)
When in employment, after-tax income must be spent on childcare, required clothing and transport for example. These additional costs must be taken into account when analysing the motivation to work as not to do so could underestimate the incentives to take-up paid employment. Using data from the Irish Household Budget Survey, this paper takes a two-stage logit model and Hausman selection model to control for selection effects to estimate the additional costs an employed CES faces compared to an unemployed CES. The main finding is that the additional costs of working are highly significant at nearly exteuro7000 per year without children; increasing to nearly exteuro9000 per year with one child under the age of five. These substantial additional costs seriously hamper work incentives as it is shown that there is a 25-fold increase (without young children) in the number of individuals who have a higher income when unemployed than when in employment with the inclusion of these additional costs of working.
Keywords: 330; costs of working; work incentives